How Teachers integrate Dashboards into their Feedback Practices - Carolien Knoop-van Campen; Inge Molenaar (EARLI, 2020)
In technology empowered classrooms teachers receive real-time data about students' performance and progress on teacher dashboards. Dashboards have the potential to enhance teachers' feedback practices and complement human-prompted feedback that is initiated by teachers themselves or students asking questions. However, such enhancement requires teachers to integrate dashboards into their professional routines. How teachers shift between dashboard- and human-prompted feedback could be indicative of this integration. We therefore examined in 65 K-12 lessons: i) differences between human- and dashboard-prompted feedback; ii) how teachers alternated between human- and dashboard-prompted feedback (distribution patterns); and iii) how these distribution patterns were associated with the given feedback type: task, process, personal, metacognitive, and social feedback. The three sources of feedback resulted in different types of feedback: Teacher-prompted feedback was predominantly personal and student-prompted feedback mostly resulted in task feedback, whereas dashboard-prompted feedback was equally likely to be task, process, or personal feedback. We found two distribution patterns of dashboard-prompted feedback within a lesson: either given in one sequence together (blocked pattern) or alternated with student- and teacher-prompted feedback (mixed pattern). The distribution pattern affected the type of dashboard-prompted feedback given. In blocked patterns, dashboard-prompted feedback was mostly personal, whereas in mixed patterns task feedback was most prevalent. Hence, both sources of feedback instigation as well as the distribution of dashboard-prompted feedback affected the type of feedback given by teachers. Moreover, when teachers advanced the integration of dashboard-prompted feedback in their professional routines as indicated by mixed patterns, more effective types of feedback were given.